Electrochemical Formation of Gold Nanoparticles on Polycrystalline Gold Electrodes during Prolonged Potential Cycling. Issue 6 (23rd November 2017) - Ahrens, Paula; Zander, Manfred; Hasse, Ulrich; Wulff, Harm; Jeyabharathi, Chinnaya; Kruth, Angela; Scholz, Fritz
Abstract: The voltammetric behavior of polycrystalline gold electrodes in 0.1 M sulfuric acid and the influence of prolonged repetitions of oxidation and reduction cycles at different scan rates on the surface morphology was studied. Slow (0.1 V s −1 ) as well as fast (1.0 V s −1 ) scan rates lead to an intense roughening of the electrode surface and the formation of a variety of different crystalline particles on it. These crystallites, their formation, and the influence of surface pretreatment were investigated with electrochemical methods, X‐ray diffraction measurements, and scanning electron microscopy. Additionally, an interpretation of the changing electrochemical signals of polycrystalline gold during prolonged potential cycling is given. Abstract : Be diligent : Prolonged potential cycling of polycrystalline gold electrodes in sulfuric acid solution leads to the formation of immobilized gold nanocrystals on the electrode surface. Electrochemical methods, X‐ray diffraction, and scanning electron microscopy are bundled to shed light on these crystallites, their formation, and the influence of surface pretreatment.